Peran Motivasi dalam Hubungan Kompetensi dan Keputusan Karir Gen Z - Umamy, Septy; Laili, Januariya; Saibah, Saibah (LPPM Universitas BSI, 2024)
Gen Z tends to have specific preferences regarding the type of work, leaning towards jobs that offer quick income or flexibility in terms of time and location. The significance for IMM is in how student organizations such as IMM can offer comprehension and backing for these career paths, while also providing a forum to exchange insights and experiences linked to the professional world. This investigation seeks to assess the correlation between Gen Z's career choices and abilities, along with the impact of motivation as a mediating factor influencing career decisions. The research adopts an explanatory quantitative approach with a sample of 100 participants, employing the Partial Least Squares (PLS) method for analysis using the statistical tool SmartPLS version 3.0. The findings indicate that competence does not partially influence Gen Z's career decisions, but it does partially influence motivation. Additionally, motivation partially influences Gen Z's career decisions. Furthermore, motivation is capable of mediating the relationship between competence and Gen Z's career decisions.